Implementation of heutagogy based learning on Bawean Island - Nurdianah, Lutfiyan (At- Ta'lim : Jurnal Pendidikan, 2025)
Heutagogy-based learning can be a learning design solution that can accommodate the diverse potential of learners. By understanding and applying heutagogy, educators can develop learning designs that maximise the potential of each learner. This heutagogy approach is more flexible with a classroom management style that gives full rights to learners. However, the application of a theory definitely requires proof in order to be implemented globally. Therefore, this research was conducted to explore and observe the implementation of heutagogy-based learning in Merdeka Curriculum. This research uses descriptive qualitative research with the research subject of 3rd grade students of UPT SDN 347 Gresik on Bawean Island. Based on the observation results, it shows positive results and very good categories. In addition, students look very active during learning. However, despite the positive observation results, there are several challenges in implementing this heutagogy-based learning, such as the uneven ability of reflection and self-evaluation among students, which leads to the recommendation that it takes adjustments to implement heutagogy learning, especially in low grades (A Phase).